CONCEPTUAL METAPHOR IN FOOTBALL NEWS ON GOAL.COM - Surahman, Fauzi Akbar; Rosalinah, Yanti; Alhaq, Muhammad Wafdan (Universitas Islam Sumatera Utara, 2024)
This research examines conceptual metaphors as defined by Lakoff and Johnson, focusing on three types: structural, ontological, and orientational. The study analyzes an editorial from Goal.com titled,